Haar wavelet collocation method for solving stagnation point over a nonlinearly stretching/shrinking sheet in a hybrid nanofluid with slip effect - Hasanah, N. S.; Rasedee, A. F. N.; Bachok, N.; Wong, T. J.; Hasan, M. (Lviv Polytechni National University, 2023)
The study of stagnation point flow and heat transfer over a stretching/shrinking sheet in a hybrid nanofluid has potential applications in a variety of fields. In order to investigate the properties of fluid flow and heat transfer, this study must solve the governing mathematical model(partial differential equations). By utilizing similarity variables, the model is transformed into a system of ordinary differential equations. The study employs a novel numerical scheme that combines the power of Haar wavelets with the collocation method to solve these ordinary differential equations. Through this approach, the study can predict several important values related to the fluid's flow and heat transfer, including the skin friction coefficient, local Nusselt number, and the profiles of velocity, temperature which can be influenced by the governing parameters of the model.